Cover Feature: Phenylene Bridged Cyclic Azaacenes: Dimers and Trimers (Chem. Eur. J. 27/2018). Issue 27 (20th April 2018) - Hahn, Sebastian; Koser, Silke; Hodecker, Manuel; Seete, Pascal; Rominger, Frank; Miljanić, Ognjen Š.; Dreuw, Andreas; Bunz, Uwe H. F.
Abstract : Several macrocyclic, phenylene‐bridged azaacenes were obtained by condensation or Buchwald–Hartwig couplings in a two‐step synthesis. We evaluated the optical and electronic properties, used the targets as emitting materials in OLEDs and discuss their properties through comparison with their linear and cyclotetrameric counterparts. The graphic illustrates the versatility of our systems. Single crystal structures of our target molecules with different substitution and functionalities are shown. More information can be found in the Full Paper by U. H. F. Bunz et al. onpage 6968 .